Media Audio Visual sebagai Alat Peraga pada Penyampaian Firman bagi Anak Usia 4-6 Tahun di Sekolah Minggu GKKK Bandung - Albert Stefanus; Basana Nababan (PT. Penerbit Tiga Mutiara, 2024)
Pandemic conditions have caused several elements in society, including the economy, health and especially education to change. So that shifts and innovations are needed, one of which is teaching techniques in Sunday school to help teachers convey the Word of God in class. Such as the use of props that can help teachers convey stories to children in class. The use of props that involve IT or audio visual media-based technology such as videos, televisions, slides is expected to attract children’s attention so that they can understand the essence of the story. The teaching of audio-visual media is inspired by the teaching method that the Lord Jesus applied when teaching the crowds and His disciples, “Look at the birds of the sky who neither plant nor reap nor gather into barns” (Matthew 6:34). In teaching, the Lord Jesus often used natural media as a way for Him to convey His Word. This research discusses the role of audio visual media used by teachers in delivering various topics. This research uses a qualitative approach with descriptive methods. Based on this research, it is concluded that the role of audio-visual media is so great in helping Sunday school teachers in teaching to be easily accepted and understood by children and recorded more easily in children’s memory.